EdCrunch: International Conference on New Educational Technologies - Kiyassov N.M (Moscow State University of Psychology and Education, 2018)
The paper gives an overview of EdCrunch, the International Conference on New Educational Technologies, focusing on its key topics and main fields of work. The Conference will be held in October 1-2, 2018. The paper stresses the importance of the Conference and its impact on each and every level of education when it comes to applying new learning technologies in education.